Biomarkers of Volume Overload and Edema in Heart Failure With Reduced Ejection Fraction - Chiorescu, Roxana Mihaela; Lazar, Roxana-Daiana; Buksa, Sándor-Botond; Mocan, Mihaela; Blendea, Dan (Frontiers in Cardiovascular Medicine, 2022)
Abstract: From a pathogenetic point of view, heart failure (HF) is characterized by the activation of several neurohumoral pathways with a role in maintaining the cardiac output and the adequate perfusion pressure in target organs and tissues. Decreased cardiac output in HF with low ejection fraction causes activation of the sympathetic nervous system, the renin angiotensin aldosterone system, arginine-vasopressin system, natriuretic peptides and endothelin, all of which cause water and salt retention in the body. As a result, patients will present clinically as the main symptoms: dyspnea and peripheral edema caused by fluid redistribution to the lungs and/or by fluid overload. By studying these pathophysiological mechanisms, biomarkers with a prognostic and therapeutic role in the management of edema were identified in patients with HF with low ejection fraction. This review aims to summarize the current data from the specialty literature of such biomarkers with a role in the pathogenesis of edema in HF with low ejection fraction. These biomarkers may be the basis for risk stratification and the development of new therapeutic means in the treatment of edema in these patients. Objectives: Our aims were to summarize the main pathophysiological mechanisms underlying the hydro-saline retention and the production of edema in HF with reduced ejection fraction (HFrEF), to highlight the main biomarkers with prognostic and therapeutic role deriving from these pathophysiological processes.